The History of Laweyan Batik Village as the Oldest Batik Industry in Surakarta - Renggani, Devi; Jhosha, Dhamay (HISTORIA: Jurnal Program Studi Pendidikan Sejarah, 2024)
This study aims to: (1) Knowing the history of Laweyan Batik Village, (2) Knowing the development of Laweyan Batik into a batik industry center, (3) Knowing the role of the community and government in supporting the existence of Laweyan Batik Village. The research method used is the historical method with stages: (1) heuristics, (2) source criticism, (3) interpretation, (4) historiography. The results show that Laweyan Batik Village is one of the most famous cultural areas in Surakarta. Laweyan Batik Village is a unique batik industry center area, and is a legendary historical site in Indonesia because it is the oldest batik industry center in Surakarta. One of the evidences that show that laweyan batik is the oldest batik in Surakarta is found in Mahkota batik which is the original batik from laweyan. Although in its development Laweyan batik village experienced ups and downs, Laweyan batik village still exists until now, it is supported by the role of the community and government agencies so that the existing cultural heritage remains sustainable.